2007
DOI: 10.1007/s00247-007-0626-7
|View full text |Cite
|
Sign up to set email alerts
|

Fractional anisotropy in white matter tracts of very-low-birth-weight infants

Abstract: Background Advances in neonatal intensive care have not yet reduced the high incidence of neurodevelopmental disability among very-low-birth-weight (VLBW) infants. As neurological deficits are related to white-matter injury, early detection is important. Diffusion tensor imaging (DTI) could be an excellent tool for assessment of white-matter injury. Objective To provide DTI fractional anisotropy (FA) reference values for white-matter tracts of VLBW infants for clinical use. Materials and methods We retrospect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
44
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(47 citation statements)
references
References 33 publications
2
44
1
Order By: Relevance
“…These results are in accordance with results from Dudink et al (2007), who found correlation between gestational age and FA in the posterior limb of the internal capsule in VLBW infants, but found no correlation between MD and gestational age.…”
Section: Correlation Analysissupporting
confidence: 92%
See 1 more Smart Citation
“…These results are in accordance with results from Dudink et al (2007), who found correlation between gestational age and FA in the posterior limb of the internal capsule in VLBW infants, but found no correlation between MD and gestational age.…”
Section: Correlation Analysissupporting
confidence: 92%
“…When studied at term, preterm infants with mechanical ventilation for more than 2 days had significant decreases in FA in the genu of corpus callosum (Anjari et al, 2009). Significant correlation has also been found between gestational age at birth and FA in the posterior part of the internal capsule at term equivalent age (Anjari et al, 2009;Dudink et al, 2007), and between FA and birth weight and gestational age in the external/extreme capsule, corpus callosum and fornix in adolescents (12-17 years) (Nagy et al, 2009). These previous studies together with our results demonstrate that the WM areas with deranged microstructure associated with low birth weight, low gestational age, and mechanical ventilation are the same at birth and in early adulthood.…”
Section: Correlation Analysismentioning
confidence: 98%
“…During normal brain development, the ADC of the white matter was shown to decrease together with a steady increase in anisotropy (Huppi et al 1998a;Neil et al 1998;Dudink et al 2007). Following a hypoxic-ischemic injury, ADC also decreases, resulting in values that are much reduced compared with the age-and region-dependent normal values (Rutherford et al 2004;McKinstry et al 2002b).…”
Section: Diffusion Tensor Imaging Studiesmentioning
confidence: 99%
“…In particular, anisotropy is highest and mean diffusivity is lowest in the commissural pathways, followed by projectional and association pathways. 39,41 In addition, anisotropy is higher and mean diffusivity is lower in the primary motor pathway compared to that in the primary sensory pathway. 38 The rate of increase in anisotropy occurring between 28 and 43 weeks is more rapid in subcortical portions of projectional pathways compared to the deep, more compact parts of projectional pathways.…”
Section: Diffusion Studies In Premature Neonatesmentioning
confidence: 99%